(untitled) (African Journal of Biomedical Research, 2023)
The prevalence of asthma has continued to increase globally and despite new guidelines and drugs, there is still a failure of control. The aim of this study was to assess the determinants of Lung Function test indices among adult asthmatics attending the Tertiary hospital. The study was a cross-sectional study conducted at the University College Hospital, Ibadan, Nigeria. A simple random sampling technique with computer-generated random numbers was used to recruit 355 patients. Spirometry was done with handheld Spirobank II (Medical International Research USA, Inc) after withholding a short-acting inhaled beta-agonist for at least six hours before the test. With each of the patients sitting comfortably, and after an initial familiarisation with the machine, the spirometry was carried out. Data were analysed using SPSS version 23. The Chi-square test was used to analyse association between categorical variables and correlation analyses was used to analyse relationships between continuous variables. Linear regression and ordinal logistic regressions were used to determine the predictors of lung function tests. A p-value of ≤ 0.05 was considered to indicate statistical significance. Three hundred and fifty-five patients who met the criteria for recruitment were interviewed. The mean age of the respondents was 39.04 (SD+ 11.335) years. For every 1 unit increase in age, there was a statistically significant increase in Forced expiratory volume per second (FEV1) % predicted by about 0.318 units (95%CI=0.116-0.520, p=0.002). Also, after adjusting for other variables, the predictor of FEV1 % predicted was sex and occupation. Females were about 2.5 times less likely to have severe asthma than males (OR= 0.397; 95% CI= 0.253-0.621). For every 1 unit increase in body mass index (BMI), there was a statistically significant increase in peaked expiratory flow rate (PEFR)% predicted by about 0.714 units (95%CI= 0.118-1.314, p=0.019). Also, for every 1 unit increase in age, there was a statistically significant increase in PEFR% predicted by about 0.354 units (95%CI= 0.153-0.555, p=0.001). In conclusion, after adjusting for other variables, lung function test indices increased with age and body mass index. The female sex and the Professionals were less likely to have severe asthma than males and unskilled workers respectively.